Modelagem das regiões brasileiras segundo o modelo econômico-demográfico de acessibilidade - Tereza Cristina de Azevedo Bernardes Faria (2015)
It's been a long time since that discussions involving the concept of region and the regionalization process surfaced and became important. Much has been said about each one according to the relevance of each line of geographical knowledge, economic and social, among others. Before all this context the aim is present and compare regionalization and their respective regions, in mesorregional and macro-regional levels, using models inspired by the Gravitational Model, the Economic and Demographic Integrated Model and Economic and Demographic of AccessibilityModel. The two models in question explore the relationship between the sum of the yield masses of emigrants and immigrants and Euclidean distance between two micro regions, at first, and soon after to accessibility, between the years 1986 and 2010. Visually the results were similar in mesorregional level, however, when viewed through the tables was realized that there were some changes involving, mainly the micro-regions of Southeast, Northeast and South, where there is a greater flow of population exchanges. The changes in the macro-regional level were higher, especially in relation to macro-region of influence of São Paulo, confirming the hegemony of the state capital. In addition, this study shows that each regionalization has unique characteristics that depend on the study target and goal of every researcher.